2001
DOI: 10.1046/j.1365-2710.2001.00337.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioequivalence evaluation of two brands of cefaclor 500 mg capsules: quantification of cefaclor using solid phase extraction technique

Abstract: Recocef was judged bioequivalent to Ceclor and the two products can therefore be considered to be interchangeable in medical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…From previous studies, it was reported that C max (mg mL À1 ) for the given doses was 18.16, 102, 78.7, and 70 mg mL À1 for cefaclor, cefotaxime, cefepime, and meropenem, respectively. [46][47][48][49] Chromatograms obtained from selected plasma samples are shown in Fig. 2.…”
Section: Results Of Methods Application To Real Human Plasma Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…From previous studies, it was reported that C max (mg mL À1 ) for the given doses was 18.16, 102, 78.7, and 70 mg mL À1 for cefaclor, cefotaxime, cefepime, and meropenem, respectively. [46][47][48][49] Chromatograms obtained from selected plasma samples are shown in Fig. 2.…”
Section: Results Of Methods Application To Real Human Plasma Samplesmentioning
confidence: 99%
“…Blood samples of 5 mL were collected at the specied time of each drug (t max ) (t max of cefaclor ¼ 50 min., cefotaxime ¼ 2-5 min., cefepime ¼ 30 min., and meropenem ¼ 5-6 min. [46][47][48][49] ) in heparinized tubes and centrifuged at 4000 rpm immediately aer receipt. The separated plasma samples were stored at À20 C till the time of analysis.…”
Section: Administration Of the Studied Drugs And Collection Of Plasmamentioning
confidence: 99%
“…SIL-IS was seldom used in previous assays of cefaclor quantification in human plasma (Chen et al, 2003(Chen et al, , 2012Huang, Cadwallader, & Heltsley, 2014;Jiang et al, 2009;Kai et al, 2003;Koytchev et al, 2004;Li et al, 2010;Lindgren, 1987;Naz et al, 2017;Qu et al, 2022;Tutunji et al, 2001). As an ideal method for precise quantification using LC-ESI-MS/MS (Huang, Cadwallader, & Heltsley, 2014), SIL-IS has almost similar physical and chemical properties, retention times, and ionization to the analyte (Liu et al, 2019;Loos et al, 2016).…”
Section: Pharmacokinetics Studymentioning
confidence: 99%
“…The uses of glimepiride as the second generation of sulphonylurea have some benefit in the effectivity in low dose, long duration, and the lower risk in older patients [5][6]. Monitoring and evaluation of the plasma level of these drugs are crucial for individual dose, pharmacokinetics as well as in bioequivalence studies [7][8][9].…”
Section: Introductionmentioning
confidence: 99%